Disruption of a long-range cis-acting regulator for Shh causes preaxial polydactyly - Lettice, Laura A. (The National Academy of Sciences, 2002)
Preaxial polydactyly (PPD) is a common limb malformation in human. A number of polydactylous mouse mutants indicate that misexpression of Shh is a common requirement for generating extra digits. Here we identify a translocation breakpoint in a PPD patient and a transgenic insertion site in the polydactylous mouse mutant sasquatch (Ssq). The genetic lesions in both lie within the same respective intron of the LMBR1/Lmbr1 gene, which resides ≈1 Mb away from Shh. Genetic analysis of Ssq reveals that the Lmbr1 gene is incidental to the phenotype and that the mutation directly interrupts a cis-acting regulator of Shh. This regulator is most likely the target for generating PPD mutations in human.